2018
DOI: 10.1177/0960327118756721
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of oxidative stress of platelets among chronic heroin and hashish addicts

Abstract: Considering the contribution of drug's route of administration, drug's pharmacokinetics, and kinetics of circulatory platelet, we concluded that chronic heroin addiction is associated with significant levels of oxidative stress to platelet's proteins and lipids. Due to the high proteomic contents of platelets, protein's oxidative stress is more prominent compared to lipids. Chronic hashish smoking is not associated with significant levels of oxidative stress in platelet's proteins and lipids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…A major emphasis was on the immunological properties of leukocytes [ 13 ]. Chronic heroin addiction is associated with oxidative stress on platelet lipids and proteins [ 10 ]. Herein, we aimed to investigate the effects of oxidative stress on the most prominent cellular blood component, erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major emphasis was on the immunological properties of leukocytes [ 13 ]. Chronic heroin addiction is associated with oxidative stress on platelet lipids and proteins [ 10 ]. Herein, we aimed to investigate the effects of oxidative stress on the most prominent cellular blood component, erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Heroin-mediated oxidative stress on cellular components of the blood is poorly investigated. Previously, it has been reported that chronic heroin addiction is associated with oxidative damage to platelets, as evident by increased protein carbonylation and lipid peroxidation in platelet lysates obtained from chronic heroin-addicted subjects [ 10 ]. This study aimed to investigate the impact of heroin administration on the redox status of erythrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, alpha-aminobutyric acid is closely related to depression symptoms in the elderly [ 62 ]. After heroin withdrawal, alpha-aminobutyric acid stays at low levels for a long time, which may be the result of heroin’s oxidative damage to cells [ 63 , 64 ]. Alloisoleucine is a stereoisomer of isoleucine; ketoleucine is produced by the incomplete breakdown of branched chain AAs.…”
Section: Discussionmentioning
confidence: 99%
“…The insignificant oxidative markers levels among hashish addicts might be a result of the contribution of multiple factors that represent various aspects of hashish cultivation, preparation, and hashish pharmacokinetics through the smoking route. Collectively, these factors may contribute to limited and unpredicted plasma levels of potent THC metabolites [61].…”
Section: Plos Onementioning
confidence: 99%